(untitled) (Research, Society and Development, 2022)
Productivity may differ between different production environments, being a key factor in determining the price and quality of cotton for textile products. These production differences are mainly associated with cultivars and soil physical conditions, which influence the indicative parameters of cotton productivity. Knowledge of the factors that affect the production of seed cotton and cotton fiber is important for the definition of regions with potential for the production of superior quality fibers. Thus, the aim of the present study was to determine simple linear regression analysis to explain the influence of soil physical attributes on seed and fiber cotton production. We sampled 200 points, in 100 plots, involving 13 cotton crops, distributed in the municipalities of Nova Mutum, Pedra Preta and Campo Verde, in the state of Mato Grosso, Brazil. We performed Simple Linear Regression Analysis between soil physical factors and cotton and seed and fiber production. The simple linear regression analysis explained the influence of soil physical attributes (clay, silt, sand, macroporosity, microporosity, total porosity and density) on PFC (coll, harvested form) and PF, which allowed to identify the highest percentage explained by the straight line estimated, and therefore the highest quality of adjustment was obtained for Total Porosity, while the lowest percentage was for Macroporosity for cotton seed production and fiber production.